2000
DOI: 10.1029/1999jd901067
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of atmospheric optical parameters on U.S. Atlantic coast sites, ships, and Bermuda during TARFOX

Abstract: Abstract. The Aerosol Robotic Network (AERONET) of automatic Sun/sky radiometers collected data on U.S. Atlantic coast sites, ships, and Bermuda in 1996 during the Tropospheric Aerosol Radiative Forcing Observational Experiment (TARFOX). Spatial and temporal analysis of Sun photometry data was supported by synoptic analysis of air mass evolution. The spatial distribution of aerosol optical depth is presented. In several cases the aerosol size distributions deduced from sky almucantar measurements and solar dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 21 publications
9
37
0
1
Order By: Relevance
“…Note, to have the correlation analysis results in one table (Table 2), we show the correlation coefficients of u  f(rh)/m and v  f(rh)/m with PM 2.5  f(rh)/m (e.g., left-side of equation 5 assuming Q ext H as constant); similar results are found when correlation coefficients are computed for u (or v) and PM 2.5 . The positive correlation between precipitiable water and surface PM 2.5 is consistent with some early studies that showed surface PM 2.5 is positively correlated with AOD that in turn is positively correlated with precipitiable water (Wang and Christopher, 2003;Smirnov et al, 2000). Interestingly, while horizontal wind (u) is negatively correlated surface PM 2.5 (Table 2), meridional wind (v) shows positive correlation, likely reflecting more polluted source from the south.…”
Section: Regression Analysissupporting
confidence: 78%
“…Note, to have the correlation analysis results in one table (Table 2), we show the correlation coefficients of u  f(rh)/m and v  f(rh)/m with PM 2.5  f(rh)/m (e.g., left-side of equation 5 assuming Q ext H as constant); similar results are found when correlation coefficients are computed for u (or v) and PM 2.5 . The positive correlation between precipitiable water and surface PM 2.5 is consistent with some early studies that showed surface PM 2.5 is positively correlated with AOD that in turn is positively correlated with precipitiable water (Wang and Christopher, 2003;Smirnov et al, 2000). Interestingly, while horizontal wind (u) is negatively correlated surface PM 2.5 (Table 2), meridional wind (v) shows positive correlation, likely reflecting more polluted source from the south.…”
Section: Regression Analysissupporting
confidence: 78%
“…The dependency of α on the size distribution has been widely used to distinguish among desert dust (e.g. Eck et al, 1999;Dubovik et al, 2002), urban-industrial Smirnov et al, 2000;Dubovik et al, 2002;Kubilay et al, 2003), and biomass burning aerosols (Kaufman et al, 1998;Eck et al, 1999Eck et al, , 2001Reid et al, 1999;Dubovik et al, 2002;Balis et al, 2003). Two main groups of particles can be identified in Fig.…”
Section: Instrumentation and Data Retrievalmentioning
confidence: 99%
“…Climate and meteorology have a strong influence on temporal and spatial variability in turbidity at a variety of scales. At the microscale, higher humidity can enhance hygroscopic aerosol growth (Pilinis et al, 1995;Kotchenruther et al, 1999;Kay and Box, 2000;Smirnov et al, 2000;Holben et al, 2001;Ramaswamy et al, 2001). Figure 10 demonstrates that the predominant summer maxima/winter minima turbidity trend over Germany is paralleled by a summer maxima/winter minima trend in precipitable water.…”
Section: Germanymentioning
confidence: 99%